Enhancing model composability and reusability for entity-level combat simulation: A conceptual modeling approach. (October 2017) - Seo, Kyung-Min; Hong, Wooyoung; Kim, Tag Gon
This paper presents a conceptual model design for entity-level combat simulation to enhance model composability and reusability. For conceptual modeling, we first describe the following three problem situations: (1) joint design of logical/physical modeling; (2) flexible model modification during scenario extension; and (3) cooperative modeling with different domain experts. To this end, we propose a two-dimensional model partition method for a combat entity, which partitions the combat entity depending on the functional aspect horizontally and the abstract level vertically. Thus, the proposed method guarantees transparent simplification of the combat entity and facilitates flexible model composition when simulating in the integration and the interoperation environments. Based on the proposed conceptual modeling, empirical measurements demonstrate the enhancement of model composability and reusability during scenario extension for anti-submarine warfare from static decoy to mobile decoy and from pattern-running torpedo to wire-guided torpedo simulations.